Functional Psychological Literacy of Parents and Teachers as a Condition of Effective Communication with a Child - N.N. Avdeeva; A.A. Shvedovskaya; A.D. Andreeva; I.A. Burlakova; S.N. Enikolopov; V.K. Zaretsky; E.I. Zakharova; Y.A. Kochetova; T.A. Poskakalova (Moscow State University of Psychology and Education, 2024)
The article provides a transcript of the speeches of the speakers of the Round Table "Functional psychological literacy of parents and teachers as a condition for building effective communication with a child", held at the Moscow State University of Psychological and Education on April 25, 2023. The Round Table addressed the problems of modern "psychology for life": the formation of functional psychological literacy of school teachers and parents in the sphere of communication and interaction with children. The speeches of the speakers of the Round Table were devoted to modern ideas about psychological literacy in psychology; approaches and researches in the field of formation of psychological literacy within the systems "teacher-pupil", "parent-child"; formation of functional psychological literacy of school teachers in communication with pupils; knowledge, skills, abilities of parents in interaction with a child; risk factors in the development of functional psychological literacy in communication and interaction with a child of parents and teachers in the sphere of communication and interaction with a child. Video recording of the speeches is given on the official video channel of PsyJournals.ru.